Strongyloidiasis: The Cause of Multiple Gastrointestinal Ulcers in an Immunocompetent Individual. (4th February 2014) - Sheth, Shail; Asslo, Fady; Hallit, Rabih; Sison, Raymund; Afridi, Muhammad; Spira, Robert; DePasquale, Joseph; Slim, Jihad; Boghossian, Jack
Abstract : Strongyloidiasis is a common parasitic disease in tropical regions of the world. Infection with Strongyloides stercoralis usually remains asymptomatic with peripheral eosinophilia and uncontrolled growth. Consequently, immunocompromised individuals are at a higher risk of complications of this disease. We present a case of an immunocompetent patient whose complaint of acute abdominal pain was found to be due to gastric and duodenal ulcerations. Laboratory examination revealed significantly elevated absolute eosinophil count at 11, 466/mm 3 (normal 0–700/mm 3 ). The duodenal biopsy revealed parasitic ova and adult worms suggestive of Strongyloides stercoralis nematode with increased eosinophils in the tissue. We report the first case of multiple gastric and duodenal ulcerations due to Strongyloides stercoralis in an immunocompetent patient. We suggest that the elevated eosinophil count played a central role in the pathogenesis.